Syrian Heritage Archive Project: Die Arbeiten der Jahre 2013 und 2014 - Bloch, Franziska (e-Forschungsberichte des DAI, 2023)
The “Syrian Heritage Archive Project“ deals with the digitization of analogue research data from Syria. It captures research projects and scholarly archives of the DAI and the Museum of Islamic Art, seeks to prepare the information in a structured manner and to make it available through the various electronic data processing systems of iDAI.world (iDAI.objects, iDAI.gazetteer, iDAI. geoserver, iDAI.bibliography). Against the backdrop of the ongoing civil war, the target application is to provide a large-scale dataset for a register of archaeological sites and historical monuments of Syria.